Pengaruh Fasilitas Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai di Kementerian Sosial Bekasi Timur - Lattifah Rahmaviani; Zahara Tussoleha Rony; Rycha Kuwara Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of work facilities and work motivation on employee performance at the Ministry of Social Affairs of East Bekasi. The type of research used in this study is quantitative research. The sampling technique uses a saturated sampling technique through a questionnaire made through a questionnaire with the criteria of all employees of the Ministry of Social Affairs of East Bekasi totaling 80 employees. The data analysis method uses multiple linear regression. The data is processed using IBM SPSS Statistic 25. The results of this study indicate that (1) Work facilities have a significant effect on employee performance at the Ministry of Social Affairs of East Bekasi, (2) Work discipline has a significant effect on employee performance at the Ministry of Social Affairs of East Bekasi and (3) Work facilities and work motivation have a simultaneous effect on employee performance at the Ministry of Social Affairs of East Bekasi.